Effect of screw access channel filling materials on uniaxial retentive force of cement-retained implant restorations - Çakan, Umut; Gültekin, Pınar; Güncü, Mustafa Barış; Canay, Senay (Wiley-Blackwell, 2014)
Background: This study aimed to investigate the effect of various abutment screw access channel filling materials on the uniaxial retention of castings cemented onto the abutment using temporary cement. Methods: Ten straight, regular platform Esthetic Abutments were used. Fifty castings were divided into five groups and the abutment screw access channels were filled with composite resin (Filtek Z 250), light-cured temporary filling (Clip), temporary filling (Coltosol), polyvinyl siloxane impression material (Elite H-D), or polytetrafluoroethylene (PTFE) tape. Castings were cemented and thermal cycled. A uniaxial tensile force with a cross-head speed of 5 mm/min, was applied to the castings until cement failure occurred. One-way analysis of variance was used to perform intergroup comparisons of the mean uniaxial retentive force (URF) values and Tukey's HSD test was used to determine the group causing the difference. Results: There were statistically significant differences between the mean URF values for the groups (p < 0.01). The mean URF value for the composite resin group was statistically higher than those for the other filling material groups respectively (p < 0.05). Conclusions: The retention of castings cemented to straight implant abutments using non-eugenol temporary cement may be influenced by the screw access channel filling material.
Keywords: Abutment; Cement; Implant; Screw Access Channel; Uniaxial Retention